2021
DOI: 10.1093/scan/nsab087
|View full text |Cite
|
Sign up to set email alerts
|

Social thinking is for doing: the posterior cerebellum supports predictions of social actions based on personality traits

Abstract: Can we predict the future by reading others´ minds? This study explores whether attributing others’ personality traits facilitate predictions about their future actions and the temporal order of these future actions. Prior evidence demonstrated that the posterior cerebellar Crus is involved in identifying the temporal sequence of social actions and the person’s traits they imply. Based on this, we hypothesized that this area might also be recruited in the reverse process, that is, knowledge of another person’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…As shown in Figure 8b, this activation is also located in the default/mentalizing network identified by Buckner et al (2011). Haihambo et al (2021) also found that the cerebellar lobule IX was engaged in predictions of temporal sequences of others' social actions. These findings support the idea, put forward by Guell et al (2018), that the cerebellar lobule IX/X constitutes a third representation of social cognitive processing, alongside Crus I and II as primary and secondary representations.…”
Section: Comparing the Explicit And Implicit Belief Srt Taskssupporting
confidence: 54%
See 1 more Smart Citation
“…As shown in Figure 8b, this activation is also located in the default/mentalizing network identified by Buckner et al (2011). Haihambo et al (2021) also found that the cerebellar lobule IX was engaged in predictions of temporal sequences of others' social actions. These findings support the idea, put forward by Guell et al (2018), that the cerebellar lobule IX/X constitutes a third representation of social cognitive processing, alongside Crus I and II as primary and secondary representations.…”
Section: Comparing the Explicit And Implicit Belief Srt Taskssupporting
confidence: 54%
“…Another recent meta-analysis found that a great majority (74%) of approximately 200 studies with activation in the posterior cerebellar Crus II revealed task processes involving mentalizing or self-related emotion attribution (Van Overwalle, Ma, & Heleven, 2020a). Recent fMRI studies further indicated that the posterior cerebellum was highly activated when social tasks required the generation of social action sequences, such as giving the correct chorological order of stories involving beliefs (Heleven et al, 2019), memorizing the order of actions implying traits of other people (Pu et al, 2020;Pu et al, 2021), or predicting sequential actions of persons based on their traits (Haihambo et al, 2021). Together, these studies suggest that the posterior cerebellum, especially Crus I and II, plays a critical role in identifying the sequence of social actions while inferring the mental state of other persons and may aid in anticipating and inferring others' mental states during dynamic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…D Trait-inconsistent action sequences [42]. E Trait-based action prediction [43] • Besides observing actions of others here and now, we also tested the hypothesis that the cerebellum might be a coprocessor in the service of predictive coding [23] supporting the prediction of future actions. For example, once mental state inferences are made, this can serve as a basis to anticipate future social encounters and their outcomes to our benefit, which is arguably the ultimate goal of social behavior [44][45][46].…”
Section: Beyond Action Sequencing: Social Inconsistencies and Sequenc...mentioning
confidence: 99%
“…Specifically, we investigated how information about a person's mental state (e.g., trait) might help to predict his or her future action sequences. Haihambo et al [43] explored this question by reversing the task logic of the inconsistent trait study by Pu et al [42] described above. In this novel study, participants were first given the trait of a protagonist (e.g., Fumak is dishonest), and then they had to select four out of six possible actions that were consistent with the trait information and them in the correct chronological order (Fig.…”
Section: Beyond Action Sequencing: Social Inconsistencies and Sequenc...mentioning
confidence: 99%
See 1 more Smart Citation